1992
DOI: 10.1038/360174a0
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome subunits encoded by the major histocompatibility complex are not essential for antigen presentation

Abstract: Major histocompatibility complex (MHC) class I molecules bind and deliver peptides derived from endogenously synthesized proteins to the cell surface for survey by cytotoxic T lymphocytes. It is believed that endogenous antigens are generally degraded in the cytosol, the resulting peptides being translocated into the endoplasmic reticulum where they bind to MHC class I molecules. Transporters containing an ATP-binding cassette encoded by the MHC class II region seem to be responsible for this transport. Genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
137
0

Year Published

1994
1994
2001
2001

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 32 publications
11
137
0
Order By: Relevance
“…Such peptides also appear to be better substrates for the TAP transporter on the endoplasmic reticulum (34,35). Interestingly, mutant mice with a deletion of LMP2 have a significant defect in the presentation of certain antigens on MHC class I (25), and the lymphoblast mutant lacking LMP2 and -7 may have a decreased efficiency of antigen processing (33).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such peptides also appear to be better substrates for the TAP transporter on the endoplasmic reticulum (34,35). Interestingly, mutant mice with a deletion of LMP2 have a significant defect in the presentation of certain antigens on MHC class I (25), and the lymphoblast mutant lacking LMP2 and -7 may have a decreased efficiency of antigen processing (33).…”
Section: Discussionmentioning
confidence: 99%
“…In related studies (36), we present evidence that the proteasome is the primary site for generation ofantigenic peptides. LMPs do not appear to be obligatory for antigen presentation, which can still occur in LMP-deficient 0.174 lymphoblasts (22,33). Proteasomes isolated from these cells still exhibit significant chymotryptic-like and tryptic-like activities (5).…”
Section: Discussionmentioning
confidence: 99%
“…Cell Lines-T2, T2-TAP2 (expressing rat TAP2 only), T2-TAP1 (expressing rat TAP1 only), and T2 TAP1ϩ2 (expressing rat TAP1 and TAP2) cells (39,40) were maintained in RPMI 1640 medium with 5% fetal calf serum and 1.0 mg/ml G418 (Life Technologies, Inc.). * The costs of publication of this article were defrayed in part by the payment of page charges.…”
Section: Methodsmentioning
confidence: 99%
“…Although the possiblity that the MHC-encoded subunits are essential for these processes was eliminated (Arnold et al, 1992;Momburg et al, 1992), it was recently shown that mice with a targeted deletion of the genes Imp2 or lmp7 have reduced levels of MHC class I siirface expression and present endogenous peptides inefficiently (Fehling et al, 1994;Van Kaer et al, 1994). The composition of newly synthesized 20s proteasomes is modified by the interfon(1FN)-y-induced exchange of the subunits 6 and c to LMP7 and LMP2, respectively (Yang et al, 1992;Akiyama et al, 1994a,b;Fruh et al, 1994;Belich et al, 1994).…”
mentioning
confidence: 99%